2008
DOI: 10.1038/nmat2252
|View full text |Cite
|
Sign up to set email alerts
|

Spin Rabi flopping in the photocurrent of a polymer light-emitting diode

Abstract: Electron spin is fundamental in electrical and optical properties of organic electronic devices. Despite recent interest in spin mixing and spin transport in organic semiconductors, the actual spin coherence times in these materials have remained elusive. Measurements of spin coherence provide impartial insight into spin relaxation mechanisms, which is significant in view of recent models of spin-dependent transport and recombination involving high levels of spin mixing. We demonstrate coherent manipulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
191
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(198 citation statements)
references
References 51 publications
6
191
1
Order By: Relevance
“…1). To remove the background, a signal acquired at 320 mT is subtracted from all the data following a similar procedure as reported in [17]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). To remove the background, a signal acquired at 320 mT is subtracted from all the data following a similar procedure as reported in [17]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous wave (CW) magnetic resonance techniques were also used as alternative methods to investigate spin effects in organic semiconductors [4,5,[14][15][16]. However there are very few papers on time resolved studies, in spite of the abundance of information that these techniques can provide [17,18]. Moreover most work was performed at low temperature, but it was shown that different phenomena come into play at room temperature where the magnetic resonance signal and organic magneto-resistance change sign [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 3 we used the parameters inferred for a semiconducting fluorescent polymer [17], implying w d k r .…”
Section: Strong Resonant Drive ω 1 ω Hfmentioning
confidence: 99%
“…According to experiments, this regime is characterized by very close electron-and hole-polaron g factors [10,16], relatively strong hyperfine interaction [11,16,17], relatively slow recombination from the singlet polaron pair state [7,17], relatively slow annihilation of triplet excitons from doublet triplet-polaron state [6,8], relatively long spin coherence times [16,17], weak exchange [18], and weak dipolar interaction between polaron pair or exciton-polaron spins [6,9,18], etc.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Substantial progress in this direction was made by the pulsed EDMR (pEDMR) experiments. [10][11][12][13][14][15][16] Unlike the continuous wave measurements, these experiments are capable of probing the coherent spin dynamics, and thus provide a closer view on the spin-dependent processes. Importantly, pEDMR (and pODMR) offer the implementation of various spin-echo based spectroscopic techniques in the study of organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%